Assessment on the Suitability of Planting Non-Native Peatlands Species Falcataria moluccana (Miq.) Barneby & Grimes in Rewetted Peatlands - Nuroniah, H.S.; Tata, H.L.; Martini, E.; Dewi, S. (MDPI, 2021)
Sengon (Falcataria moluccana), a fast-growing timber tree that naturally grows on mineral soils, is currently promoted in peatlands. This study aimed to (1) experimentally test the response of sengon seedlings in waterlogged conditions in the nursery; (2) describe and analyze the biophysical condition of a sengon plantation and its growth; (3) describe sengon farm practices on peatlands; and (4) identify key actor’s perception on planting sengon on peatlands. This study combined an experiment in nursery, field measurements, and key-informant interviews. The nursery experiment showed that peat soil affected seedling’s growth: survival rates decreased by 25–33% after 3 months of inundation. Sengon growth at age 1–5-years-old in peat soil was slower than that on mineral soils. Sengon growth in peatland was influenced by peat depth and peat maturity. Sengon plantation in Central Kalimantan was driven by market availability and industrial wood demand. Fourty-three percent of respondents thought sengon does not grow well in peat soils, but 57% of respondents thought that additional soil treatment will enhance site suitability. Based on key-informants’ experience, 64% disagree with sengon development in peatlands. Our study provides evidence that sengon is predominantly not suitable to be planted on peatlands. Therefore, cautions need to be taken when planting sengon on peatland areas.